Resensi Buku: Organization Strategy, Structure, and Process - Ayi Ahadiyat (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2003)
Book ReviewJudul Buku : Organization Strategy, Structure, and ProcessPenulis : Raymond E. Miles and Charles C. SnowPenerbit : McGraw-Hill Kogakusha, Ltd (International Student Edition), Tokyo, 274 hlm.Tahun : 1978